Too little, too soon [solid-state flash memories]. - Goldstein, H.
This paper discusses the disadvantages of Samsung's new NAND flash-based solid-state disks (SSD), which range in capacity from 4 to 32 GB aimed at notebook, subnotebook, and tablet computers. The NAND flash was developed to replace other storage media, especially those used in mobile products. However, because of its high price relative to hard drives, sales of NAND flash has been disappointing. Compared to Samsung's NAND flash, the read/write speeds on hard disk drives in most notebooks tend to be faster, reaching up to 80 megabytes per minute.
Keywords: Samsung NAND flash drive; Computer memory; Solid-state flash memories